Safety performance of selected bus stops in Ibadan Metropolis, Nigeria (2022)
Bus systems cannot be fully explored if issues such as safety of bus passengers on-board or at bus stops are not addressed. This study was aimed at assessing the safety of bus stops in Ibadan metropolis. Twenty bus stops were purposefully selected for this study from the five urban local government areas in Ibadan metropolis. A field survey involving interviews with 50 passengers and direct observations of hazardous acts was carried out at the bus stops. Casual factors of hazardous acts were noted as well. A score survey was conducted with 17 experts (civil engineers and transportation engineering researchers) where they were asked to rate how much each casual factor contributes to its corresponding hazardous act using a scale of 1–4 (1 being ‘not important at all’ and 4 being ‘very important’). Experts were also asked to make pairwise comparisons among hazardous acts and consistent responses were analyzed using Analytic Hierarchy process (AHP). Results from the score survey and AHP were used to model the safety levels of the selected bus stops. With safety levels ranging from 2.38 to 4.83 (10 being the best and 0 being the worst), all bus stops fell short of an acceptable level of safety. Also, Interviews conducted revealed passengers’ dissatisfaction with their user-experience. Recommendations were therefore made based on the findings.